The punitive transition in youth justice: Reconstructing the child as offender. (30th March 2020) - Case, Stephen; Bateman, Tim
Abstract: The transition from 'child' to 'offender' status can be fast‐tracked when offending is formally recognised through formal disposal, with children treated increasing punitively as they progress through the Youth Justice System. The status and 'offenderising' transitions of children who offend is socio‐historically contingent, not only on their behaviour, but on political, socio‐economic, societal, systemic and demography. We support this perspective through a periodised re‐examination of four socio‐historical trajectories in the construction of the 'youth offender': Conflict, ambivalence and bifurcation (1908‐1979); depenalising diversion and back to justice (1980‐1992), fast‐tracking the child to offender transition (1993‐2007) and tentative depenalisation (2008 to present).